Organization of Activities of Club Associations of Higher Pedagogical Educational Institutions of Ukraine : (Second half of the XX century) - Chubukina, Olena (Professional Art Education, 2021)
The purpose of the article is to analyze scientific and pedagogical sources on the problem of research and because of the analysis to cover the activities of club associations of higher pedagogical institutions of Ukraine in the second half of the twentieth century. Methodology. The activity of student clubs and scientific associations influences the formation of national self-consciousness and promotes aesthetic socialization. An important way to solve the above problems is to comprehend and realize the rich experience, appeal to national sources in higher pedagogical educational institutions of Ukraine in the second half of the twentieth century, the creative use of which will contribute to the growth of educational potential of our society. The study of free time, ways and means of its organization is the object of study of various sciences: philosophy, culturology, sociology, pedagogy, psychology, history. The scientific literature widely uses the terms "club", "student club", "activity", but there is a certain diversity in the interpretation of these concepts. In our study, we define activity as a specific way of human attitude to the world around us, which is the driving force and condition of social progress. The scientific novelty is that an attempt is made to define the concept of "club" in the field of club science. We believe that the club should be considered as a multifunctional association, the main task of which is integration, meeting the needs of visitors in meaningful leisure in the name of common goals, interests, local communication, self-education and cultural and creative realization of the individual. Shows the chronology of the development of club activities in institutions of higher education. Results scientific research proves that the second half of the twentieth century In Ukraine is characterized by the emergence of numerous club associations of higher pedagogical institutions. Higher pedagogical institutions of education in Ukraine have accumulated considerable experience in organizing the leisure of student youth, the functioning of club associations. In Soviet times (the so-called "golden age" of Soviet pedagogy - 60-90 years of the twentieth century.) Forms and methods of organizing youth leisure were developed, which are almost inviolable in our time, and are the object of many historical and pedagogical explorations. Beginning in the 1960’s, one can observe the flourishing of the activities of youth clubs, which were understood as complex universal centers of leisure activities for young people. Such structures were widely developed in the 60-70’s of the twentieth century, and in the 80-90’s style and methods of work, despite the new socio-cultural conditions and demands of young people) did not change, so new alternative clubs began to appear, where youth activities were less formalized. Activities of student clubs in higher educational institutions of Ukraine in the second half of the twentieth century. was a multifunctional cultural and educational process organized by the teaching staff based on the general concept of educational work of a particular educational institution. It was based on the principle of voluntary participation in such activities and was collective in nature. However, the activities of the student club depended entirely on the socio-cultural and political development of the society of that time, its moral, ethical and spiritual values. Conclusions. The main centers of club associations in the study period were educational institutions for young people, based on which various youth clubs developed their activities. They did not require large material resources and corresponded to age, national and regional characteristics. The main purpose of club associations in higher educational institutions was the education and self-education of students based on initiative, creative manifestation of everyone’s abilities. Tasks were aimed at organizing socially useful youth leisure, finding new forms and means of cultural and mass work in accordance with the interests and needs of young people, involvement in cultural and mass leisure activities, development of socio-cultural creativity, ensuring youth communication because of joint activities and cultural recreation.